ИНЖЕНЕРНО-ГЕОМОРФОЛОГИЧЕСКИЕ УСЛОВИЯ ТЕРРИТОРИИ ГОРОДА КРАСНОДАРА - Антошкина Е.В. (My University, 2004)
On the basis of complex geomorphologic and hydrogeological investigations the area of Krasnodar city was districted in accordance with different fitness for building and people living. The main part of the city is characterized by favorable conditions, but the new districts are in danger of ground water rise. The analysis of engineering-geomorphologic conditions has let to develop concrete proposals concerning the improvement of situation.
Keywords: 551.438.5(470.62)